Efektivitas Penggunaan Obat Asma Bronkial Dalam Menormalkan Nilai Hemoglobin Darah, Frekuensi Pernafasan dan Denyut Nadi - Nur Hasanah; Nazla Nazla (STIKes Kharisma Persada, 2020)
Asthma is a chronic inflammatory disease characterized by episodic wheezing, coughing, and tightness in the chest due to obstruction of the respiratory tract which can be characterized by an excessive response from the trachea and bronchi to various stimuli. Bronchial Asthma at the Outpatient Installation Bhineka Bakti Husada Hospital for the period April - June 2018. This research is a descriptive non-experimental study. The method of collecting data retrospectively by looking at the source of Bronchial Asthma patient medical record data. The number of patients analyzed was 45 patients who met the inclusion criteria, namely having a diagnosis of Bronchial Asthma and therapy using drugs. Broccial asthma patients consisted of 30 (66.7%) female patients and 15 (33.3%) male patients. The most diagnosed patients with asthma in the age range of youth (18-45 years) as many as 35 patients. The drugs used are bronchodilator and corticosteroid groups. Salbutamol which is included in the sympathomimetic group is the most effective drug in normalizing the patient's Hb value. Methyl prednisolone included in the cortkosteroid group is the most effective drug in normalizing the respiratory frequency (tachypnea) and tachycardia values to normal.